Challenges of International Adoption in Bosnia and Herzegovina - Duraković, Anita (Medicine, Law & Society, 2023)
Adoption is a special form of family-legal protection of children without parental responsibility, which establishes the parental relationship. We distinguish adoption that takes place within the borders of one country, i.e. internal adoption, and cross-border adoption, i.e. international adoption. The international element can appear in subjects of adoption, i.e. with regard to their citizenship, domicile or habitual residence, and the place of adoption. The focus of the work is the legislative framework in Bosnia and Herzegovina for cases of international adoption, especially the situation of establishing the international adoption of a domestic citizen in Bosnia and Herzegovina and the situation of establishing the international adoption of a foreign citizen abroad in the service of child healthcare and child welfare. Considering the numerous challenges that exist in this matter, the existence of a complete and high-quality normative framework is a condicio sine quo non for successful and legally valid international adoption. In this context, and aware of the importance of the Hague Convention on Adoption from 1993 and the need to harmonize the legislation of Bosnia and Herzegovina with the acquis of the European Union and the comparative trends in comparative law, proposals for lege ferenda were made.